2021
DOI: 10.1007/s12350-020-02079-3
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and hemodynamic reactivity during cardiac stress testing: The role of gender and age in myocardial ischemia

Abstract: Background. The prevalence of myocardial ischemia is associated with anxiety. State and trait anxiety are more common in younger women compared to men, and high anxiety levels could affect hemodynamic reactivity during cardiac stress testing. The aim is to examine whether anxiety plays a role in gender differences in patients £ 65 and > 65 years in hemodynamic reactivity and ischemia during cardiac stress testing. Methods and results. Included were 291 patients (66.8 ± 8.7 years, 45% women) with suspect ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…The association between acute emotions and ischemia during MPI is likely [20][21][22][23][24][25] , but evidence to date is based on self-reported emotions only. The unique aspect of this study is the measurement of acute emotions using facial expression recognition software during cardiac stress testing as part of MPI 26 . It is unknown whether acute negative emotions measured during cardiac stress testing are associated with the presence or absence of anginal complaints reported during cardiac stress testing in patients with (suspect) CMD.…”
Section: Introductionmentioning
confidence: 99%
“…The association between acute emotions and ischemia during MPI is likely [20][21][22][23][24][25] , but evidence to date is based on self-reported emotions only. The unique aspect of this study is the measurement of acute emotions using facial expression recognition software during cardiac stress testing as part of MPI 26 . It is unknown whether acute negative emotions measured during cardiac stress testing are associated with the presence or absence of anginal complaints reported during cardiac stress testing in patients with (suspect) CMD.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce bias related to multicollinearity, the joint effects of emotional states and psychological background factors were examined for each psychological background factor separately. We also explored potential interaction terms with sex, consistent with our prior report based on this study (33), and examined interactions between the facial emotion expression measures and each of the psychological background factors as related to myocardial ischemia, to examine potential synergy between these two domains of assessment. ORs with 95% confidence intervals (CIs) are reported for logistic regression analyses.…”
Section: Statistical Analysesmentioning
confidence: 98%
“…[8]. If we consider differences associated with gender, studies consistently show that females have more anxiety [9]. Pre-pandemic factors also should be considered; the literature has shown that patients commonly experience stress when undergoing dental treatment.…”
Section: Introductionmentioning
confidence: 99%